2014
DOI: 10.1101/gad.236869.113
|View full text |Cite
|
Sign up to set email alerts
|

CTCF regulates the human p53 gene through direct interaction with its natural antisense transcript, Wrap53

Abstract: The multifunctional CCCTC-binding factor (CTCF) protein exhibits a broad range of functions, including that of insulator and higher-order chromatin organizer. We found that CTCF comprises a previously unrecognized region that is necessary and sufficient to bind RNA (RNA-binding region [RBR]) and is distinct from its DNA-binding domain. Depletion of cellular CTCF led to a decrease in not only levels of p53 mRNA, as expected, but also those of Wrap53 RNA, an antisense transcript originated from the p53 locus. PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
189
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(222 citation statements)
references
References 37 publications
31
189
2
Order By: Relevance
“…A recent study reported that CTCF maintains p53 expression and promotes p53 function in the DNA damage response through epigenetic regulation and binding to the antisense transcript originated from the p53 locus (27), suggesting that the RNA-binding properties of CTCF may play a role in DNA damage repair. Here we found that recruitment of CTCF to sites of DNA damage did not depend on the RNAbinding domain of CTCF, and that RNase A did not disrupt the association of CTCF and other DDR proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that CTCF maintains p53 expression and promotes p53 function in the DNA damage response through epigenetic regulation and binding to the antisense transcript originated from the p53 locus (27), suggesting that the RNA-binding properties of CTCF may play a role in DNA damage repair. Here we found that recruitment of CTCF to sites of DNA damage did not depend on the RNAbinding domain of CTCF, and that RNase A did not disrupt the association of CTCF and other DDR proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The full-length CTCF molecule was divided into several sections, and RFP tags were added (26,27) (Fig. S3D).…”
Section: Ctcf Prevents Genomic Instabilitymentioning
confidence: 99%
“…Additionally, CTCF has a more direct influence on transcription; 7-14% of CTCF sites are found within promoter proximal regions (4). Functionally, there is evidence that CTCF acts primarily as a transcriptional activator in these cases, and it is unclear that its transactivating capabilities are dependent on epigenetic processes (5)(6)(7)(8); when bound within exonic regions, it promotes polymerase II (Pol II) pausing (9), adding another level of transcriptional regulation to its repertoire.…”
mentioning
confidence: 99%
“…Recently, by using PAR-CLIP, Ricardo et al [117] reported CTCF can bind a variety of RNAs in vivo. Moreover, they found CTCF can regulate p53 expression via binding Wrap53 RNA, which is an antisense transcript originating from the p53 locus.…”
Section: Studying Epigenetic Modification-associated Rnasmentioning
confidence: 99%